Strategy for increasing Internal Audit Capability on Inspectorate of Jember Regency - PUTRA, TEGUH; Ma’mun Sarma; Lukman M. Baga (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2023)
One of Indonesia’s Government way to eradicate corruption throughout the region is to increase Internal Audit Capability Model at the Provincial/District/City Inspectorate. Petrașcu dan Tieanu (2014) stated that internal audit has various responsibilities to support management in building anti-fraud/corruption mechanisms, assessing fraud risks at the organizational and business process levels, assessing connections between fraud risks and internal control, supporting auditor efforts in fraud investigations and reporting to the audit committee. The East Java Province BPKP Representative's assessment of the business processes of the Jember Regency Inspectorate until the end of 2022 concluded that the Jember Regency Inspectorate only obtained level 2 IACM (Internal Audit Capability Model). This research aims to analyze several factors that influence internal audit capability, evaluate business processes and formulate strategies that the Jember Regency Inspectorate can use to improve its intenal audit capability. Strategy formulation is carried out by analyzing key organizational factors using the IE, SWOT and QSPM matrices. The research results show to improve supervisory governance, share knowledge regarding supervision, develop policies/SOPs related to independence, monitor follow-up results of supervision and recruit auditors.